Genetic parameter estimates for litter traits in Jakhrana breed of Indian goat - Yogesh C. Bangar; Ankit Magotra; A.S. Yadav (Reproduction and Breeding, 2023)
The litter size and litter weight are the most important indicators of growth production system in goats as they are directly related to the survival and growth of the kids. The present attempt was made to estimate genetic parameters of litter traits such as litter size at birth (LSB), litter size at weaning (LSW), litter weight at birth (LWB) and litter weight at weaning (LWW) of Jakhrana breed of Indian goat. These traits were subjected to study variation due to direct additive genetic effects by adjusting non-genetic factors under linear mixed model. The data of litter records of 101 Jakhrana goats including pedigree information were processed and the results showed that the least-square means for LSB, LSW, LWB and LWW were 1.20 ± 0.05, 1.19 ± 0.05, 3.08 ± 0.11 and 12.11 ± 0.49, respectively. The direct heritability estimates for LSB, LSW, LWB and LWW were 0.17, 0.01, 0.001 and 0.10, respectively. The genetic (0.70–0.97) and phenotypic (0.61–0.92) correlation estimates among litter traits were high and positive. This study indicated that the additive variation among the early reproductive traits was low in range which does not provide a warrant for the improvement through selection. However, the evaluation of these traits has provided the current state of litter performance of Jakhrana goat which may be upgraded by managerial practices specially care and feeding of pregnant goats.